Initiatives for a New Normal Library - Manabat, April (Nazarbayev University Library, 2020)
Presentation during the Western Mindanao State University Webinar last 25 June 2020. This presentation aims to define what s the new normal in the library setting, to determine the importance to rethink some processes and adapting to changes, and to discuss the basic and practical initiatives for a new normal library.
Keywords: new normal; library; pandemic